RF transceiver reference design for third generation W-CDMA cellular handset - Wong, , SK; Lee, , SW; Sim,, ML (2005)
A radio frequency transceiver reference design for. Third Generation UTRA/FDD W-CDMA cellular handset is presented in this paper. A number of commercial RFICs are analyzed by considering the heterodyne architecture implementation of the transceiver. Requirements and considerations in the cellular handset radio frequency transceiver design are also discussed. Numerical analysis and measurement results obtained in this work could be used as a reference design for immediate RF transceiver hardware implementation in commercial 3G W-CDMA cellular handsets.